2012
DOI: 10.1016/j.watres.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic shift of polyphosphate-accumulating organisms with different levels of polyphosphate storage

Abstract: ElsevierAcevedo Juárez, B.; Camiña, C.; Corona, JE.; Borrás Falomir, L.; Barat Baviera, R. (2015). The metabolic versatility of PAOs as an opportunity to obtain a highly P-enriched stream for further P-recovery. Chemical Engineering Journal. 270:459-467. doi:10.1016/j.cej.2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(87 citation statements)
references
References 53 publications
9
71
1
3
Order By: Relevance
“…Previous studies suggested that these two clades used the glycolytic and TCA cycle differently under anaerobic conditions (Wexler et al, 2009;Oehmen et al, 2010a;Acevedo et al, 2012). Although we did not detect any apparent genome-level differences, we did note instances where the gene copy number for a particular enzyme important in the TCA cycle varied, which could influence expression levels.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Previous studies suggested that these two clades used the glycolytic and TCA cycle differently under anaerobic conditions (Wexler et al, 2009;Oehmen et al, 2010a;Acevedo et al, 2012). Although we did not detect any apparent genome-level differences, we did note instances where the gene copy number for a particular enzyme important in the TCA cycle varied, which could influence expression levels.…”
Section: Discussioncontrasting
confidence: 66%
“…One bioreactor revealed enhanced TCA cycle gene expression aerobically, whereas the other showed enhanced synthesis anaerobically, suggesting that these two Accumulibacter populations had distinct anaerobic and aerobic metabolisms. Another study explored the impact of polyphosphate content on anaerobic performance and stoichiometry, and found that when polyphosphate content decreased in the cells, Clade IIA appeared to switch to a glycogen-accumulating metabolism, which no longer assisted in removing phosphate from the system (Acevedo et al, 2012). These findings suggest that distinct Accumulibacter clades inhabit different niches in EBPR ecosystems, each providing an important role in ecosystem function.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 5, the COD removal efficiency in anaerobic tank was significantly higher than that in other tanks, accounting for 85.9% of total COD removal rate (92.5%) in the BNR-IC system, which is agreement well with the characteristic of DPAO (Acevedo et al 2012). In anaerobic condition, carbon source, especially VFA, was taken up by DPAO and stored them as PHB, resulting in the P release from the cells of DPAO.…”
Section: Performance Of Bnr-ic Process In Each Stagesupporting
confidence: 68%
“…PAOs/DPAOs can use poly-P and/or glycogen to supply energy, while GAOs/DGAOs have no poly-P pool and so can only use glycogen to supply energy [22]. EPS are a potential energy supply for organisms in starvation situations [6].…”
Section: Proposed Mechanism Of Microorganism Spatial Distribution mentioning
confidence: 99%
“…GAOs therefore may have a tendency to use EPS rather than PAOs in a starvation scenario, and tend to crush from granules in situations where EPS are consumed as an energy and carbon source for GAOs aggregation [22].…”
Section: Proposed Mechanism Of Microorganism Spatial Distribution mentioning
confidence: 99%